2019
DOI: 10.1128/mbio.01833-19
|View full text |Cite
|
Sign up to set email alerts
|

Lotus japonicus Symbiosis Genes Impact Microbial Interactions between Symbionts and Multikingdom Commensal Communities

Abstract: Studies on symbiosis genes in plants typically focus on binary interactions between roots and soilborne nitrogen-fixing rhizobia or mycorrhizal fungi in laboratory environments. We utilized wild type and symbiosis mutants of a model legume, grown in natural soil, in which bacterial, fungal, or both symbioses are impaired to examine potential interactions between the symbionts and commensal microorganisms of the root microbiota when grown in natural soil. This revealed microbial interkingdom interactions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 56 publications
10
58
1
Order By: Relevance
“…These families included Burkholderiaceae, which contained some species able to form symbiosis with a certain legumes from the Papilionoideae subfamily [83,84] and also some species dominate soybean nodule [85] or known as a plant growth-promoting strain in non-legume plants [86]. Our results are consistent with other studies that found also a depletion of Burkholderiales in the roots of Lotus symbiosis pathway gene mutants [40,41]. Therefore, we suggest that the effective symbiosis promotes the enrichment of bene cial microbes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These families included Burkholderiaceae, which contained some species able to form symbiosis with a certain legumes from the Papilionoideae subfamily [83,84] and also some species dominate soybean nodule [85] or known as a plant growth-promoting strain in non-legume plants [86]. Our results are consistent with other studies that found also a depletion of Burkholderiales in the roots of Lotus symbiosis pathway gene mutants [40,41]. Therefore, we suggest that the effective symbiosis promotes the enrichment of bene cial microbes.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, disrupting symbiosis between B. diazoe ciens and soybean signi cantly reduced bacterial diversity in the rhizosphere and rhizoplane. This result is in line with a recent study on plant SYM mutants documenting a reduction of fungal diversity [41]. Together, these studies suggest that functional symbiosis favors a more diverse root microbiota.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicated the genetic traits that control rhizobium symbiosis might be also involved in the regulation of fungal community or rhizosphere fungi (Genre and Russo, 2016). Consistent with our results, a recent paper showed that the key genes in the symbiotic signaling pathway significantly influenced the enrichment of some fungi in both rhizosphere and within the roots (Thiergart et al, 2019).…”
Section: Soybean Nodulation Is Associated With Rhizosphere Fungal Comsupporting
confidence: 91%
“…However, how maize mycorrhizal microbial community homeostasis is affected by functional AM symbiosis traits is elusive. Recent studies performed with mycorrhizal Lotus japonicus mutants disrupted in the common symbiosis signaling pathway (CSSP) or downstream processes showed that an almost complete depletion of Glomeromycotina taxa and impaired arbuscule formation in roots were accompanied by an enrichment of few Ascomycota fungi and shifts in bacterial communities under greenhouse conditions [42,43]. On the other hand, knocking out CSSP genes didn´t affect the life cycle of the growth-promoting basidiomycete fungus Piriformospora indica (also known as Serendipita indica) in L. japonicus nor did silencing of CCaMK affect bacterial or fungal communities in roots of field-grown Nicotiana attenuata [44,45].…”
Section: Introductionmentioning
confidence: 99%